A hybrid robust‐stochastic approach for optimal scheduling of interconnected hydrogen‐based energy hubs. Issue 2 (20th March 2021) - Mansour‐Satloo, Amin; Agabalaye‐Rahvar, Masoud; Mirazaei, Mohammad Amin; Mohammadi‐Ivatloo, Behnam; Zare, Kazem; Anvari‐Moghaddam, Amjad
Abstract: The energy hub (EH) concept is an efficient way to integrate various energy carriers. In addition, demand response programmes (DRPs) are complementary to improving an EH's efficiency and increase energy system flexibility. The hydrogen storage system, as a green energy carrier, has an essential role in balancing supply and demand precisely, similar to other storage systems. A hybrid robust‐stochastic approach is applied herein to address fluctuations in wind power generation, multiple demands, and electricity market price in a hydrogen‐based smart micro‐energy hub (SMEH) with multi‐energy storage systems. The proposed hybrid approach enables the operator to manage the existing uncertainties with more flexibility. Also, flexible electrical and thermal demands under an integrated demand response programme (IDRP) are implemented in the proposed SMEH. The optimal scheduling of the hydrogen‐based SMEH problem considering wind power generation and electricity market price fluctuations, as well as IDRP, is modelled via a mixed‐integer linear programming problem. Finally, the validity and applicability of the proposed model are verified through simulation and numerical results.